2015
DOI: 10.1371/journal.pone.0122904
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein-A1 as a Damage-Associated Molecular Patterns Protein in Osteoarthritis: Ex Vivo and In Vitro Pro-Inflammatory Properties

Abstract: Osteoarthritis (OA) is associated with a local inflammatory process. Dyslipidemia is known to be an underlying cause for the development of OA. Therefore, lipid and inflammatory levels were quantified ex vivo in blood and synovial fluid of OA patients (n=29) and compared to those of rheumatoid arthritis (RA) patients (n=27) or healthy volunteers (HV) (n=35). The role of apolipoprotein A-I (ApoA1) was investigated in vitro on inflammatory parameters using human joint cells isolated from cartilage and synovial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…After 24 h of starvation, cells were incubated with oxidized human LDL (h-oxLDL; 50 μg·mL À1 ) or with a pool of serum from the control group of our rabbit model (4% HFD serum) for 24 h to become foam cells. The final amount of TC and LDL in the cell culture was in the same range as those expected in the synovial fluid of RA patients (65 mg·mL À1 of TC and 60 mg·mL À1 of LDL) (Oliviero et al, 2009;Oliviero et al, 2012;De Seny et al, 2015). Cells were then stimulated for 24 h with recombinant human IFNγ (50 ng·mL À1 ) in presence or absence of tofacitinib dissolved in DMSO at different doses (CP-690550; Pfizer International, Peapack, NJ, USA).…”
Section: Experimental Conditionsmentioning
confidence: 65%
“…After 24 h of starvation, cells were incubated with oxidized human LDL (h-oxLDL; 50 μg·mL À1 ) or with a pool of serum from the control group of our rabbit model (4% HFD serum) for 24 h to become foam cells. The final amount of TC and LDL in the cell culture was in the same range as those expected in the synovial fluid of RA patients (65 mg·mL À1 of TC and 60 mg·mL À1 of LDL) (Oliviero et al, 2009;Oliviero et al, 2012;De Seny et al, 2015). Cells were then stimulated for 24 h with recombinant human IFNγ (50 ng·mL À1 ) in presence or absence of tofacitinib dissolved in DMSO at different doses (CP-690550; Pfizer International, Peapack, NJ, USA).…”
Section: Experimental Conditionsmentioning
confidence: 65%
“…Supporting this notion, a study has shown that synovial fluid of OA patients showed dysregulated lipid profile and correlated with inflammatory parameters in the OA joint cavity. The same authors demonstrated that APOA‐1 expression as well as HDL and LDL concentrations would influence the inflammatory properties of cholesterol regulating gene APOA‐1 in chondrocytes and fibroblast‐like synoviocytes . Another study has demonstrated that sterol regulatory element binding proteins (SREBPs), a key transcription factor regulating cholesterol metabolism, is involved in OA pathogenesis .…”
Section: How Could Cholesterol Damage the Cartilage?mentioning
confidence: 97%
“…The same authors demonstrated that APOA-1 expression as well as HDL and LDL concentrations would influence the inflammatory properties of cholesterol regulating gene APOA-1 in chondrocytes and fibroblast-like synoviocytes. 48 Another study has demonstrated that sterol regulatory element binding proteins (SREBPs), a key transcription factor regulating cholesterol metabolism, is involved in OA pathogenesis. 17 In a recent study, importance of hedgehog signaling in chondrocytes has been demonstrated in regulating cholesterol homeostasis.…”
Section: How Could Cholesterol Damage the Cartilage?mentioning
confidence: 99%
“…Obesity-related hyperlipemia is characterized by low systemic levels of high-density lipoprotein (HDL) and high levels of total cholesterol (TC), triglyceride (TG), and oxidized low-density lipoprotein (ox-LDL) [ 9 ]. Previous studies have pointed out that high serum TC and TG levels and lack of HDL have been linked to progression of cartilage loss in knee OA [ 10 , 11 ]. In particular, lack of HDL predisposes mice to osteoarthritis following long-term exposure to high-fat diet (HFD) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%